Масова людина та проблема психагогіки в умовах поглиблення антропологічної кризи - Городиська, Ольга Миколаївна (Національний юридичний університет ім. Ярослава Мудрого, 2018)
Стаття присвячена проблемі аналізу та можливого подолання антропологічної кризи у сучасному світі. Приділено увагу явищу масової людини, яка характеризується відірваністю знання, яке набуло характеру індустрії, від буття людини, що лише поглиблює кризу, враховуючи вплив технічного компоненту. Пропонується впровадження психагогіки як засобу виховання людини і як умови зміни уявлень про людське.

Problem setting. The anthropological crisis in XX–XXI centuries led human to the edge of extinction as metaphysical so actual. The problem became especially aggravated in Post-structuralism and Post-modernism as well as with emergence of the transhumanism. Today there is no philosophic doctrine proposing the real ways of the crisis negotiation but they ought to be built otherwise human will have no future in its philosophical meaning. Recent research and publications analysis. One of the first who claimed and substantiated the anthropological crisis was E. H. Usserl. Concerning the problems of mass society, popular culture and mass human specifying the anthropological crisis we have to name the researches of Frankfurt School thinkers, K. Jaspers, O. S. Pengler, H. M. Enzensberger, J. B. Audrillard, others. The attention has to be paid to the J. Ortega y Gasset who formulated the concepts of «mass society» and «mass human» and who identified these phenomena with the anthropological crisis. The M. B. Uber’s and M. Foucault’s works were useful to explain the anthropological crisis essence and to build the new human life strategy in particular with the Foucault’s elaboration of the psychagogie. Paper objective. The general analysis of the anthropological crisis, the detection of the interdependency between the crisis and mass society, popular culture and mass human phenomena could be named as the aims of the article. To show the abruption between the human being and the knowledge production which is turned into the consciousness industry are also the task of the research. To bear in mind the technical factor and its influence on the anthropological crisis deepening the article is also aimed at the research of psychagogie as the possible way of the human formation. Paper main body. The development of the western civilisation naturally formed the mass society and mass human phenomena. Mass human is mediocrity with no genius. As a product of a mass society mass human is characterised by the continual increasing of the needs and by the inborn ingratitude to everything that realises those needs. Such paradox transformed human into the product of popular culture. Counting technical component and the productive character of the knowledge receiving its necessary to interpret human as a result of the consciousness industry when any knowledge is considered to be unfamiliar to the human being, not enrooted into the human life. So progress in knowledge is transformed into the simple accumulation, it doesn’t influence on the human being, and the truth of human life is lost. To overcome the anthropological crisis and to avoid the further abruption between the human being and the knowledge as the essence of the modernity it is proposed to change the way of human formation by implementation of the psychagogie. This method is considered to be not only the way of human nurturing but as well the condition of changing the notion about human. Conclusions of the research. The anthropological crisis is deepening and civilisation doesn’t propose the exit from this situation. So one of the ways of its overcoming is to implement the new approach into the nurturing system using psychagogie as the true philosophical basis of the human self-consciousness.
Mass human and the psychagogie problem in the conditions of the anthropological crisis deepening
Keywords: суспільство; культура масова; свідомість; психагогіка; society; popular culture; consciousness; psychagogie